A New One-Step Iterative Process for Common Fixed Points in Banach Spaces - Jong Kyu Kim; Safeer Hussain Khan; Mujahid Abbas (Journal of Inequalities and Applications, 2008)
We introduce a new one-step iterative process and use it to approximate the common fixed points of two asymptotically nonexpansive mappings through some weak and strong convergence theorems. Our process is computationally simpler than the processes currently being used in literature for the purpose.